Pengukuran indeks kualitas kebijakan pada pelayanan panggilan kedaruratan 112 di Kota Probolinggo - Fitria, Nurul Jannah Lailatul (Journal of Law, Administration, and Social Science, 2024)
Quality policies need to be formed, especially those related to public services that must be carried out by the government through public service innovation through the use of technology. One of the policies that need to be considered is the policy on the use of a single number for emergency calls, 112. Emergency calls for special services to the public who handle emergency conditions. It is this urgency that requires measuring policy quality to find out that policies related to emergency calls are indeed good and deserve to be implemented. As in Probolinggo City, the NTPD 112 service is contained in Mayor Regulation No. 175 of 2019 concerning Amendments to Mayor's Regulation No. 155 of 2018 concerning the Implementation of Services for Probolinggo City Emergency Call Number 112. There are 11 service handling policies in the regulation. Research with descriptive quantitative approach. Researchers conducted research on measuring the quality of the NTPD 112 policy in Probolinggo City with the IKK principle. The research sample was determined by 4 policies from 11 policies through formulas and methods by the State Administration Institute. The measurement uses two variables, namely Policy Planning and Policy Utilization Evaluation with an interval scale measurement of 1-10. The calculation results show that 45% of the value of the Policy Planning process is 3,651 and 55% the value of the Policy Benefit Evaluation process is 4,747. This results in a Policy Quality Index of 8.398. This shows the categorization of the policy quality index. So the quality of the policy for the single number emergency call 112 Probolinggo City is in the "B" quality with the "Good" category. Kebijakan berkualitas dalam model pelayanan pemerintahan pada masyarakat mengorientasikan pada penerapan dengan inovasi pelayanan publik melalui pemanfaatan teknologi. Khususnya pada kualitas kebijakan pelayanan penggunaan nomor tunggal panggilan darurat 112. Panggilan darurat khusus pelayanan pada masyarakat yang menangani kondisi darurat. Urgensi inilah yang membutuhkan pengukuran kualitas kebijakan untuk mengetahui bahwa kebijakan yang berkaitan dengan panggilan kedaruratan memang baik dan layak diterapkan. Seperti di Kota Probolinggo, pelayanan NTPD 112 tertuang pada Peraturan Walikota Nomor 175 Tahun 2019 Tentang Perubahan Atas Peraturan Walikota Nomor 155 Tahun 2018 Tentang Penyelenggaraan Layanan Nomor Tanggal Panggilan Darurat 112 Kota Probolinggo. Terdapat 11 kebijakan penanganan pelayanan pada regulasi tersebut. Riset dengan pendekatan kuantitatif deskriptif. Peneliti melakukan riset pengukuran kualitas kebijakan NTPD 112 di Kota Probolinggo dengan prinsip IKK. Sampel riset ditentukan 4 kebijakan dari 11 kebijakan melalui rumus dan metode oleh Lembaga Administrasi Negara. Pengukuran menggunakan dua variabel yakni Perencanaan Kebijakan dan Evaluasi Pemanfaatan Kebijakan dengan pengukuran skala interval 1-10. Hasil perhitungan menunjukkan 45% dari nilai proses Perencanaan Kebijakan sejumlah 3,651 dan 55% nilai proses Evaluasi Kemanfaatan Kebijakan sejumlah 4,747. Sehingga menghasilkan Indeks Kualitas Kebijakan sebesar 8,398. Hal ini menunjukkan kategorisasi indeks kualitas kebijakan. Maka Kualitas kebijakan NTPD 112 Kota Probolinggo masuk pada kategori tingkat “B” dengan arti berkualitas “Baik”.